The Unpleasant Taste of Death: The Challenge of Industrial Livestock to Literature - Simon, Anne (Colloquia, 2022)
Industrial livestock production with its communication strategy aimed at concealing a filthy death and the bad taste of the meat produced has become an important motif in contemporary literature. How to create a narrative about the quiet life of animals that blend in a large herd? A life that is ruthlessly framed by a beginning (insemination) and an end (slaughter) lacks deviation and adventure—it lacks the possibility of becoming the material for a novel. The aim of this article is to examine the poetic devices and ethical aspirations of an emerging genre called the ‘agroalimentary novel,’ which depicts animals for profit and recreates their unique existence worthy of a story. Agroalimentary novels have become increasingly common in Europe and the Americas in the last decade. They raise the issue of taste very plainly: in Latin (gustus) and Old French (in the 12th c., gost and in the 13th c., goust), ‘taste’ is understood literally and figuratively, and is linked to the sense and appreciation of taste. The meaning of taste is associated with aesthetics, and not only with the senses, but also with art, not only with the body, but also with social issues; it refers to both practical activities and norms. How do the themes of livestock production and slaughterhouses relate to the issue of taste? Writers and readers find the aesthetics of the traditional novel problematic. When depicting it, some become inarticulate, while others are confronted with the inability to talk about it. In both cases, they confront the impossible symbolic act of appropriation. Loathing and disgust that is physically expressed and less humanly focused, even more distinctly than in the work of Jean Paul Sartre or in the various accounts of war, have entered literature.
Keywords: zoopoetics; taste; industrial animal agriculture; literature